GM-CSF Inhibits c-Kit and SCF Expression by Bone Marrow-Derived Dendritic Cells - Barroeta Seijas, Amairelys Belen; Simonetti, Sonia; Vitale, Sara; Runci, Daniele; Quinci, Angela Caterina; Soriani, Alessandra; Criscuoli, Mattia; Filippi, Irene; Naldini, Antonella; Sacchetti, Federico Maria; Tarantino, Umberto; Oliva, Francesco; et al. (Frontiers in Immunology, 2017)
Stem Cell Factor (SCF), the ligand of c-kit, is a key cytokine for hematopoiesis. Hematopoietic precursors express c-kit, whereas differentiated cells of hematopoietic lineage are negative for this receptor, with the exception of NK cells, mast cells and a few others. While it has long been recognized that dendritic cells (DCs) can express c-kit, several questions remain concerning the SCF/c-kit axis in DCs. This is particularly relevant for DCs found in those organs wherein SCF is highly expressed, including the bone marrow (BM). We characterized c-kit expression by cDCs from BM, and demonstrated a higher proportion of c-kit+ cells among cDC1s than cDC2s in both humans and mice, whereas similar levels of c-kit expression were observed in cDC1s and cDC2s from mouse spleen. To further study c-kit regulation, DCs were generated with GM-CSF from mouse BM, a widely used protocol. CD11c+ cells were purified from pooled non-adherent and slightly adherent cells collected after 7 days of culture, thus obtaining highly purified BM derived DCs (BMdDCs). BMdDCs contained a small fraction of c-kit+ cells, and by re-plating them for 2 days with GM-CSF we obtained a homogeneous population of c-kit+ CD40hi MHCIIhi cells. Not only did BMdDCs express c-kit, but they also produced SCF, and both were striking up-regulated if GM-CSF was omitted after re-plating. Furthermore, a small but significant reduction in BMdDC survival was observed upon SCF silencing. Incubation of BMdDCs with SCF did not modulate antigen presentation ability of these cells, nor it did regulate their membrane expression of the chemokine receptor CXCR4. We conclude that the SCF/c-kit mediated pro-survival circuit may have been overlooked because of the prominent use of GM-CSF in DC cultures in vitro, including those human DC cultures destined for the clinics. We speculate that DCs more prominently rely on SCF in vivo in some microenvironments, with potential implications for Graft Versus Host Disease (GVHD) and anti-tumor immunity.